Structure–Function Relationship of the Interaction between Tissue Factor and Factor VIIa - Gajsiewicz, Joshua M.; Morrissey, James H. (Seminars in Thrombosis and Hemostasis, 2015)
Interactions between tissue factor and factor VIIa are the primary initiators of coagulation in hemostasis and certain thrombotic diseases. Tissue factor, an integral membrane protein expressed extensively outside of the vasculature, is the regulatory protein cofactor for coagulation factor VIIa. Factor VIIa, a trypsin-like serine protease homologous with other blood coagulation proteases, is weakly active when free in solution and must bind its membrane-bound cofactor for physiologically relevant activity. Tissue factor allosterically activates factor VIIa by several mechanisms such as active site positioning, spatial stabilization, and direct interactions with the substrate. Protein–membrane interactions between tissue factor, factor VIIa, and substrates all play critical roles in modulating the activity of this enzyme complex. Additionally, divalent cations such as Ca2+ and Mg2+ are critical for correct protein folding, as well as protein–membrane and protein–protein interactions. The contributions of these factors toward tissue factor–factor VIIa activity are discussed in this review.
Keywords: tissue factor; factor VIIa; protein–membrane interactions; extrinsic tenase; metal ions